Implementação numérica da função de transição aplicada ao modelo de predição de Cheung em ambientes interiores - Heitor Oliveira Ferreira Santos (2023)
The present paper provides an evaluation of a new numerical implementation method for calculating the Fresnel integral in electromagnetic scattering problems. The specific application presented here is the improvement of techniques for predicting radio coverage in indoor environments: the Cheung and Seidel-Rappaport models are modified by including the new numerical implementation of the Fresnel integral in the formulation of diffraction coefficients. The applicability of the new implementation is also verified in the solution of the canonical problem of scattering from a conducting half-plane.